1985
DOI: 10.1111/j.1346-8138.1985.tb02855.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Eosinophil Chemotactic Factor in the Blister Fluid of Patient With Incontinentia Pigmenti

Abstract: A case of incontinentia pigmenti associated with tissue and peripheral blood eosinophilia was reported. Eosinophil chemotactic factor (ECF) with low molecular weight was detected in the blister fluid at 17 days after birth by an in vitro chemotactic assay. ECF showed two different molecular weights; one was approximately 1355 daltons and the other much smaller. A similar factor was also detected in the content of a suction blister in clinically uninvolved skin at 2 months after birth. Investigations of ECF gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, the mechanism by which eosinophils accumulate in IP is not yet fully understood. Investigations into the pathomechanism of IP uncovered an unidentified eosinophil chemotactic factor in the blister fluid of patients with IP and also in the extracts of their crusted scales [9,10]. Eotaxin, a CC class chemokine, is a recently identified eosinophil‐selective chemokine [11–16].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the mechanism by which eosinophils accumulate in IP is not yet fully understood. Investigations into the pathomechanism of IP uncovered an unidentified eosinophil chemotactic factor in the blister fluid of patients with IP and also in the extracts of their crusted scales [9,10]. Eotaxin, a CC class chemokine, is a recently identified eosinophil‐selective chemokine [11–16].…”
Section: Introductionmentioning
confidence: 99%
“…Although some of these ECFs are thought to be operative at the lesional skin o f dermatoses character ized by eosinophil infiltration, there are only a few papers reporting the determination of these factors in such dermatoses. Low molecular weight ECFA-likc substances were demonstrated in the blisters of bullous pemphigoid [6], incontinentia pigmenti [7], or drug eruption, and in the suction blisters fluids obtained from the lesional skin of atopic derm atitis cases [8],…”
Section: Eosinophil Chemotactic Factor and Se Baceous Glandsmentioning
confidence: 99%
“…Schmalstieg et al (19) noted the presence of basophils in early vesicular lesions of incontinentia pigmenti and suggested that their presence may be a mechanism of eosinophii recruitment into tissues through histamine and eosinophii chemotactic factor release. Tsuda et al (20) demonstrated the presence of eosinophii chemotactic factor in the blister fluid of patients with incontinentia pigmenti. In 1986 Takematsu et al (21) reported the presence of eosinophii chemotactic activity in extracts of crusted scales from patients whose disease was in the vesiculobullous stage.…”
Section: Discussionmentioning
confidence: 99%